Scientific financial management : advances in intelligence capabilities for corporate valuation and risk assessment - Glantz, Morton (AMACOM, 2000)
"This book teaches you how to deploy the complete array of advanced, technology-actualized financial tools available today. These sophisticated methods are the new tools of choice to crystallize value drivers, explain optimal capital allocation strategies, develop hedging strategies, and otherwise deliver the goods to your CEO and the board of directors."--BOOK JACKET.